A VARIETY OF AMPHIBIANS AND REPTILES LIVING IN THE FISH FARMING OF BUKHARA - Safarova Zakiya Teshayevna; Aripov Bakhtiyor Pharmonovich (Western European Studies, 2024)
The article describes information on the diversity of vertebrate animals, namely amphibians and reptiles found on the territory of the Bukhara fishing industry. There is a taxonomic analysis, taxonomy and description of the vertebrates found in the territory. listed in the Red Book of Uzbekistan
Keywords: vertebrates; taxonomy; group; amphibians